Penguatan Pengetahuan Masyarakat tentang Hubungan Penyakit Infeksi Anak dengan Stunting dan Keterampilan membuat Hand Sanitizer di Desa Bukit Raya, Kecamatan Cempaga Hulu, Kabupaten Kotawaringin Timur, Kalimantan Tengah - Seth Miko; Nawan nawan; Septi Handayani (LPPM Universitas Palangka Raya, 2023)
East Kotawaringin still has a high stunting rate in Central Kalimantan in 2022. Bukit Raya Village is one of the villages in the Cempaga Hulu District, East Kotawaringin Regency. In addition to the problem of stunting in the East Kotawaringin Regency area, that there are still cases of diarrhea in toddlers and acute respiratory disease with complaints of coughing. Therefore, it is necessary to hold activities to strengthen public knowledge regarding the relationship between infectious diseases (diarrhea and acute respiratory infections) with stunting and to improve skills in making materials to support clean and healthy behavior in the form of hand sanitizers/liquid soap with kecombrang as the basic ingredient. This strengthening activity was carried out in the village of Bukit Raya, involving 30 participants and attended by local village officials with counseling and training method. The results of the activity evaluation showed an increase in knowledge about infectious diseases related to diarrhea and acute respiratory infections, their prevention, and their relationship to stunting. In addition, there was also an increase in the participants' knowledge and skills in making kecombrang-based hand sanitizer.